Riparian zone management and rehabilitation in Malaysia through restorative justice - Zainudin, Zaki; Ansari, Abdul Haseeb; Baharudin, Harnani (AENSI Publications, 2013)
One of the main contributing factors of riparian zone destruction in Malaysia is the encroachment of river reserves by oil palm plantations.Although there are conventional legal mechanisms that deal with the issue, much of the damage has already been incurred.Pollutants such as fertilizers, pesticides and total suspended solids (SS) are freely transported to a river in these encroached areas. Sg. Kalumpang in Sabah can register turbidity in excess of 200 NTUs, whereas TSS in Sg. Tiram in Johor was above 100 mg/L. Emphasis on rehabilitation would be more beneficial instead of the conventional punitive approach.The restorative justice concept provides an avenue for this as curative/corrective measures on the part of the offender is given emphasis. For the concept to be practical, several steps have to be taken, that includes inculcation of the restorative justice concept into existing regulations, increasing compound fees for existing environmental contraventions (as a deterrent), exclusion from penalization on the part of the offender if the restorative justice route was taken, as well as stakeholder involvement and coordination. To fully reap the benefits, the concept must also be retrospective of existing environmental damages.